Results of the intraoperative alpha defensin lateral flow test in the second stage of revision hip arthroplasty - Valery Yu. Murylev; Javad Parvizi; Alexander I. Rudnev; Grigory A. Kukovenko; Pavel M. Elizarov; Aleksey V. Muzychenkov; Semen S. Alekseev; Dmitriy O. Golubkin; Konstantin G. Yakovlev; Anastasia O. Ugolnikova (Гений oртопедии)
Background Alpha defensin lateral flow (ADLF) test is a current accurate tool for detecting/excluding periprosthetic joint infection (PJI); however, its usage in patients with a hip joint spacer has not yet been fully studied. The purpose of the study was to determine the diagnostic parameters (accuracy, specificity, sensitivity, AUC) of the alpha-defensin lateral flow test as part of the reinfection verification in patients with a hip joint spacer in the second stage of revision hip arthroplasty (RHA). Material and methods In a prospective study the effectiveness of the intraoperative use of ADLF test was evaluated in 105 patients with hip joint spacers during the 2nd stage of revision hip arthroplasty (RHA). The standard microbiological examination of intraoperative samples of tissues and synovial fluid was accepted as the gold standard for re-infection diagnosis. Results The growth of microflora according to the results of intraoperative microbiological examination was detected in 24 (23 %) cases. The discrepancy in the results of intraoperative microbiological examination and the results of the ADLF test was found in 10 (11 %) cases. False positive and false negative cases were identified. ADLF test demonstrated 96.39 % specificity, 89.52 % accuracy and 63.64 % sensitivity. The AUC index was 0.8. Discussion ADLF test has good diagnostic indicators for the verification of PJI in patients after hip replacement. The use of ADLF test in patients with a hip joint spacer who continue antibacterial therapy allows the test to be performed in the 2nd stage of RHA. However, the results of ADLF test in patients during the 2nd stage of RHA show that additional studies are required. Conclusion The ADLF test, despite the divergent data from scientific publications, demonstrates high diagnostic value for intraoperative verification of reinfection in patients with a hip joint spacer, allowing timely correction of treatment tactics. "Dry tap", bloody synovial fluid, as well as weakly virulent coagulase‑negative microflora, including in microbial associations, are limitations of the ADLF test application.